Bioprocess considerations for T‐cell therapy: Investigating the impact of agitation, dissolved oxygen, and pH on T‐cell expansion and differentiation. Issue 10 (6th July 2020) - Amini, Arman; Wiegmann, Vincent; Patel, Hamza; Veraitch, Farlan; Baganz, Frank
Abstract: Adoptive T‐cell therapy (ACT) has emerged as a promising new way to treat systemic cancers such as acute lymphoblastic leukemia. However, the robustness and reproducibility of the manufacturing process remains a challenge. Here, a single‐use 24‐well microbioreactor (micro‐Matrix) was assessed for its use as a high‐throughput screening tool to investigate the effect and the interaction of different shaking speeds, dissolved oxygen (DO), and pH levels on the growth and differentiation of primary T cells in a perfusion‐mimic process. The full factorial design allowed for the generation of predictive models, which were used to find optimal culture conditions. Agitation was shown to play a fundamental role in the proliferation of T cells. A shaking speed of 200 rpm drastically improved the final viable cell concentration (VCC), while the viability was maintained above 90% throughout the cultivation. VCCs reached a maximum of 9.22 × 10 6 cells/ml. The distribution of CD8+ central memory T cells (TCM ), was found to be largely unaffected by the shaking speed. A clear interaction between pH and DO ( p  < .001) was established for the cell growth and the optimal culture conditions were identified for a combination of 200 rpm, 25% DO, and pH of 7.4. The combination of microbioreactor technology and Design of Experiment methodology provides a powerful tool to rapidly gain an understanding of the design space of the T‐cell manufacturing process. Abstract : Adoptive T‐cell therapy has emerged as a promising new way to treat systemic cancers such as acute lymphoblastic leukemia, yet lack of process control and characterisation remain major challenges in the manufacturing process. Here, a single‐use 24‐well microbioreactor was used in conjunction with Design of Experiment methodology to investigate the effect of varying key process parameters on the growth and differentiation of primary T cells in a perfusion‐mimic process and an optimal parameter combination was identified within the investigated design space.